The Aesthetics of Islamic Symbols And Their Use In The Drawings of Middle School Students (Journal of the College of Basic Education, 2025)
Every artist must belong to a certain environment or to a certain society, where he draws for himself a line that suits his society, environment and traditions, and is often influenced by his civilization and what he can draw from it, especially if that civilization is ancient, with clear features. Here we have institutions for a problem that requires research, and the researcher tries to answer the following question: How are Islamic symbols employed in the drawings of middle school students in Iraq? The current research aims to study Islamic symbols and employ them in the drawings of middle school students and the artistic foundations for that employment.As for the second chapter, the theoretical framework included two topics, as well as extracting and discussing indicators from it to benefit from them in formulating the research tool, where the first topic was: (Symbol in modern and contemporary art) and the second topic: (Symbol in Arab Islamic civilization(.As for the third chapter, it included the research procedures, and the fourth chapter included the results and conclusions